THE ADOPTION OF CLOUD ACCOUNTING BY MSMES: THE ROLE OF DIGITAL VISION AND ITS IMPACT ON ECONOMIC SUSTAINABILITY - Wahyudi, Sulkhanu Risqo; Purwantini, Anissa Hakim; Farida, Farida (Universitas Jember, 2024)
ABSTRACTThis study draws on the Technology-Organization-Environment (TOE) framework to investigates how digital vision, serving as a proxy for intention, influences the adoption of cloud accounting. Furthermore, it evaluates the consequent effect of this adoption on the economic sustainability of culinary Micro, Small, and Medium Enterprises (MSMEs) in the Yogyakarta Special Region. Using convenience sampling, a total of 163 culinary MSMEs that have adopted cloud accounting applications and digital payment methods were selected as the sample. The results of the study, analyzed using the SEM-PLS (Structural Equation Modeling - Partial Least Squares) technique, indicate that relative advantage, competitive pressure, and vendor support have a positive effect on digital vision. Moreover, digital vision drives MSMEs to adopt cloud accounting, which positively impacts economic sustainability. The organizational dimensions of top management support and organizational readiness were found to have no effect on the digital vision of MSMEs in the culinary sector. These findings have significant implications for MSME practitioners, the government, and cloud accounting vendors to support MSME sustainability.Keyword: digital vision; MSMEs; sustainability; TOE framework